Veterinary public health services in developing countries: guidelines to restructuring (1999)
The veterinary public health (VPH) services comprises several plans of action and serve the purpose for improving and protected human health and well-being wich is essential for the socioeconomic development of populations. The reestructuring of public sector as offerent of health services and the increase in participation of private sector are evident. This paper presents a review of the reestructuring process, its justification and framework (administration, delivery and financing) in developing countries. The direction, restrictions, and the restricted delivery view and its effects on veterinary public health services are evaluated.